The Asian Pacific Association for the Study of the Liver clinical practice guidelines for the diagnosis and management of metabolic associated fatty liver disease - Eslam, Mohammed; Sarin, Shiv K.; Wong, Vincent Wai-Sun; Fan, Jian-Gao; Kawaguchi, Takumi; Ahn, Sang Hoon; Zheng, Ming-Hua; Shiha, Gamal; Yilmaz, Yusuf; Gani, Rino; Alam, Shahinul; Dan, Yock Young; et al. (Hepatology international, 2020)
Metabolic associated fatty liver disease (MAFLD) is the principal worldwide cause of liver disease and affects nearly a quarter of the global population. The objective of this work was to present the clinical practice guidelines of the Asian Pacific Association for the Study of the Liver (APASL) on MAFLD. The guidelines cover various aspects of MAFLD including its epidemiology, diagnosis, screening, assessment, and treatment. The document is intended for practical use and for setting the stage for advancing clinical practice, knowledge, and research of MAFLD in adults, with specific reference to special groups as necessary. The guidelines also seek to improve patient care and awareness of the disease and assist stakeholders in the decision-making process by providing evidence-based data. The guidelines take into consideration the burden of clinical management for the healthcare sector.